Sequence of operations for real‐time control of microgrids and networked microgrids - Mehrdad Sheikholeslami (IET Renewable Power Generation, 2022)
Abstract Microgrids (MGs) provide a potential solution to accommodating renewable and distributed energy resources (DERs). MGs and the networked form of MGs, that is, networked MGs or NMGs, have received significant attention in the past two decades. However, several details that need to be considered for the practical operations of MGs and NMGs are often neglected in the literature. First, there is a need for a step‐by‐step sequence of operations (SOO) that clearly defines the procedures for changing the operation modes of MGs and NMGs for their reliable and resilient operation. Second, there is a need to develop a new control strategy for power exchange between networked MGs to ensure the information privacy and respect the electrical boundary of each MG. Third, there is a need for developing the model of MGs and NMGs in a real‐time simulator to safely evaluate the performance of the microgrid master controller (MMC) in making real‐time decisions and following the SOO. This paper proposes solutions for these three requirements and presents results to evaluate the performance of the proposed solutions. The IIT Campus Microgrid (ICM) and Bronzeville Community Microgrid (BCM), as well as their networked form, are selected as the practical testbeds and are modelled in real‐time digital simulator (RTDS). The RTDS model is interfaced with the MMC for real‐time data exchange and the operation of the MMC is tested to illustrate the importance of SOO in the real‐time control of MGs and NMGs.